2021
DOI: 10.1186/s13075-021-02661-1
|View full text |Cite
|
Sign up to set email alerts
|

Immune cell profiles in synovial fluid after anterior cruciate ligament and meniscus injuries

Abstract: Background Anterior cruciate ligament (ACL) and meniscus tears are common knee injuries. Despite the high rate of post-traumatic osteoarthritis (PTOA) following these injuries, the contributing factors remain unclear. In this study, we characterized the immune cell profiles of normal and injured joints at the time of ACL and meniscal surgeries. Methods Twenty-nine patients (14 meniscus-injured and 15 ACL-injured) undergoing ACL and/or meniscus surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Similarly, studies have revealed that high percentages of Th cells are present in blood samples and synovial fluid from RA and OA subjects ( Lurati et al, 2015 ; Rosshirt et al, 2019 ). Recently, Kim-Wang et al (2021) also found that the numbers of immune cells, primarily T cells with multiple Th phenotypes, are elevated in the synovial fluid following ACL and meniscus injuries, while the numbers of Th1, Th2, and Th17 cells are the dominant populations of the CD4 subsets. Furthermore, T17 cells can produce IL-17, which causes synovial fibroblasts, chondrocytes, macrophages, and osteoclasts to elicit a cascade and finally promotes inflammation, cartilage degradation, and changes in bone metabolism ( Koenders et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, studies have revealed that high percentages of Th cells are present in blood samples and synovial fluid from RA and OA subjects ( Lurati et al, 2015 ; Rosshirt et al, 2019 ). Recently, Kim-Wang et al (2021) also found that the numbers of immune cells, primarily T cells with multiple Th phenotypes, are elevated in the synovial fluid following ACL and meniscus injuries, while the numbers of Th1, Th2, and Th17 cells are the dominant populations of the CD4 subsets. Furthermore, T17 cells can produce IL-17, which causes synovial fibroblasts, chondrocytes, macrophages, and osteoclasts to elicit a cascade and finally promotes inflammation, cartilage degradation, and changes in bone metabolism ( Koenders et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that subjects diagnosed with primary OA exhibit elevated percentages of activated macrophages and T cells in peripheral blood, synovial fluid, and synovial tissues ( Li et al, 2017 ; Rosshirt et al, 2019 ). Specifically, a recent study has revealed a T-cell-predominant immune profile in the synovial fluid following ACL and meniscus injuries ( Kim-Wang et al, 2021 ). The immune cells present after joint injuries may play a vital role in the development of PTOA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within minutes of injury, the local and systemic immune response is activated. 46 , 47 Resident macrophages, natural killer (NK) cells, and fibroblasts from the synovium; lymphocytes, mast cells, and dendritic cells from the perivascular tissues; and osteoclasts from bone marrow are released by local damage stimuli. 46–48 In the first few hours, these activated cells lead to the influx of blood-borne neutrophils, monocytes, T helper cells, and B cells that enter the joint capsule to facilitate wound healing to initiate cleanup, cell proliferation, and remodeling.…”
Section: Introductionmentioning
confidence: 99%
“… 52 , 53 Resident innate NK cells also secrete cytokines, such as interferon-γ (IFN-γ) and tumor necrosis factor-alpha (TNF-α), and interact with macrophages, and other immune cells, to enhance the response. 47 , 54 These different immune and non-immune cells, through their cytokine networks, play pivotal roles both as activator cells and target effector cells to produce the correct healing response. 46 Within the joint, the synovial membrane regulates the traffic by maintaining a rich network of sympathetic and sensory nerves, blood vessels, and lymphatic vasculature to promote healing.…”
Section: Introductionmentioning
confidence: 99%